From Access to Quality: Evaluation of Inclusive Education Programs through CIPP Model-Based Systematic Literature Review - Mar'atul Hidayah Izzatul Islami; Evita Yuliatul Wahidah; Anita Aisah (Journal of Psychological Perspective, 2026)
Inclusive education aims to provide equal learning opportunities for all students, including students with special needs, within the same educational environment. Although inclusive education policies in Indonesia have expanded access to schooling, the quality of program implementation remains uneven across schools. This study aims to analyze the quality of inclusive education programs using the CIPP (Context, Input, Process, Product) evaluation framework. This study employed a Systematic Literature Review (SLR) approach following the PRISMA guidelines. Literature searches were conducted in January 2026 through Google Scholar using the keywords “inclusive education”, “program evaluation”, and “CIPP model”. The inclusion criteria covered journal articles published between 2020 and 2025 in Indonesian and English that discussed the evaluation of inclusive education programs. Five articles met the inclusion criteria and were analyzed through thematic coding based on the CIPP components. The findings show that inclusive education policies have generally been implemented in schools, but their application in classroom practice is still inconsistent. The main challenges identified across studies include limited teacher competence, shortages of special assistant teachers, inadequate adaptive learning facilities, and assessment systems that have not fully accommodated diverse learning needs. Several studies also reported positive impacts on students’ social participation and self-confidence. This review indicates that improving the quality of inclusive education requires stronger teacher preparation, adaptive learning strategies, collaborative support systems, and responsive evaluation practices.